COVID-19: An Appeal for an Intersectoral Approach to Tackle With the Emergency - Alessandra Scagliarini; Alberto Alberti (Frontiers Media S.A., 2020)
The knowledge of disease determinants is a pre-requisite for disease prevention. Infectious diseases determinants can be classified in three ways, as: primary or secondary; intrinsic or extrinsic; and associated with host, agent, or environment. In the specific case of COVID-19 several of these determinants are currently unknown leading to difficulties in public health approach to this disease. In this paper, we attempt to address several of the current gaps on COVID-19 using a systematic analysis on recent findings and some preliminary knowledge on animal coronaviruses. A discussion on the impact of COVID-19 determinants in disease prevention and control will be based on the Environmental Change and Infectious Disease (EnVID) systemic framework to address several challenges that may affect the control of the SARS- CoV-2 pandemic spread both in industrialized and in developing Countries.